UPAYA PENINGKATAN KUALITAS PELAYANAN KESEHATAN PADA IBU DAN ANAK PADA MASA PANDEMI COVID-19 DI PUSKESMAS KETAPANG NUSANTARA ACEH TENGAH TAHUN 2022 - Siti Nurmawan Sinaga (Asosiasi Sinergi Pengabdi dan Pemberdaya Indonesia (ASPPI), 2022)
Getting adequate health services is an effort to improve and improve the quality of life for the better. In this COVID-19 pandemic situation, there are many restrictions on almost all routine services including maternal and newborn health services. The service and satisfaction of pregnant women with Maternal and Child Health (KIA) services at the Puskesmas has an important role in improving maternal and child health. One of the efforts made by the government in order to accelerate the reduction in maternal mortality is quality maternal health services, namely pregnancy checks. The Pandemic period is a difficult time for health workers to provide health services due to the Covid-19 pandemic condition requiring a person to keep their distance, avoid crowds and to a minimum not to go to hospitals or health services. The purpose of this service activity is as an effort to improve the quality of maternal and child health services in antenatal care services during the Covid-19 pandemic at the Ketapang Nusantara Health Center, Central Aceh Regency in 2022. Health education in the form of health services for pregnant women during the COVID-19 pandemic can reduce risk of death for mother and baby. Health education and demonstrations about health for pregnant women were carried out for 4 weeks. After carrying out community service activities for pregnant women, it was found that there was an increase in knowledge of pregnant women about nutrition for pregnant women, the benefits of classes for pregnant women, exercise for pregnant women and yoga as well as understanding the condition and welfare of pregnant women through physical examinations. It is hoped that health workers will continue to improve the quality of health services for pregnant women.